(untitled) (Praxis Educativa, 2025)
The increase in enrollment in doctoral programs worldwide has highlighted the importance of the supervisor-thesis candidate relationship. Within this context, the article explores feedback practices from a dialogic perspective, aiming to move beyond one-way communication to create a space for exchange where doctoral students can develop their critical thinking. The analysis of fifty-nine surveys conducted with doctoral students in the Social Sciences and Humanities indicated that dialogic feedback practices are particularly prominent in the socio-affective dimension of the supervisor-student relationship, while the cognitive aspects of feedback tend to be limited to corrections and suggestions related to written work. Besides, participation in academic socialization instances fosters a dialogic relationship between students and supervisors by sharing work dynamics and practices characteristic of the academic field.